Variação no tamanho corpóreo e cantos de anúncio de hilídeos (ANURA) na Serra do Mar - Bandeira, Lucas Nicioli [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Ao longo de um gradiente altitudinal alterações climáticas como, mudanças na temperatura e umidade, podem influenciar atributos morfológicos, fisiológicos, reprodutivos e comportamentais dos animais dando origem a tendências de variação que estruturam padrões. Uma dessas tendências define uma regra ecogeográfica comumente observada que é conhecida como regra de Bergmann. Essa regra postula que os indivíduos de regiões com altas latitudes e/ou altitudes apresentam um maior tamanho corpóreo. O objetivo principal do nosso estudo é identificar os padrões de variação no tamanho do corpo e cantos de anúncio de três espécies de hilídeos (Dendropsophus minutus, Hypsiboas faber e Scinax hayii) no gradiente altitudinal da Serra do Mar do estado de São Paulo, Sudeste do Brasil. Para análise do tamanho corpóreo nós usamos um total de 324 indivíduos de D. minutus de 28 localidades, 86 de H. faber de 23 localidades e 73 de S. hayii de 13 localidades. Para as análises acústicas, foi usado um total de 10 cantos de anúncio de D. minutus de três localidades, três cantos de H. faber de duas localidades e cinco cantos de S. hayii de três localidades. Dendropsophus minutus e S. hayii apresentaram diferenças no tamanho do corpo entre as localidades ao longo do gradiente altitudinal. Para D. minutus o tamanho do corpo dos indivíduos diminuiu com o aumento da altitude, enquanto que para os exemplares da espécie S. hayii o tamanho do corpo foi maior em altas altitudes. O tamanho do corpo de H. faber foi semelhante em diferentes altitudes. Os machos de D. minutus apresentaram maiores valores nas frequências dominante e mínima nos cantos de anúncio de regiões de altas altitudes e menores valores na frequência máxima. Para S. hayii, todas as frequências diminuíram com o aumento da altitude; ao passo que os parâmetros duração...

Throughout an environmental gradient there are changes on the climate atributes, such as in temperature and humidity. These differences influence morphological, physiological, behavioral and reproductive traits of animals. One of the most studied morphological patterns in an elevational gradient is known as the Bergmann rule, meaning that at high altitudes, individuals show larger body sizes. The main objective of this study is to identify the variation patterns in body size and acoustic parameters of the advertisement calls of three species of hylids (Dendropsophus minutus, Hypsiboas faber and Scinax hayii) in an altitudinal gradient in the Serra do Mar, located at the southeastern part of the São Paulo State in Brazil. For body size analysis we measured a total of 324 individuals of D. minutus from 28 locations, 86 individuals of H. faber from 23 localitions and 73 S. hayii individuals from 13 locations. For the acoustic analysis, we sampled a total of 10 advertisement calls of D. minutus from three locations in the gradient, three calls of H. faber from two locations, and five calls of S. hayii from three locations. Dendropsophus minutus and S. hayii showed differences in body size in relation to altitudinal gradient. In D. minutus, there was a decrease in body size with the increase in altitude, while for S. hayii the body size was greater at higher altitudes. The body size of H. faber was similar at different altitudes. The advertisement calls of D. minutus showed higher dominant and minimum frequencies at elevated altitudes and a lower maximum frequency. In S. hayii all frequencies decreased with the increasing in altitude, while note duration and number of pulses per note increased. Call parameters in H. faber did not vary with altitude. The three species of hylids studied exhibit characteristics such as, for example, body size and... (Complete abstract click electronic access below)
Keywords: Ecologia animal; Anuro; Anuro - Mar, Serra do; Anfíbio - Mar, Serra do; Som produzido por animais; Bioacustica; Animal ecology